Pengaruh Sudut Potong dan Kecepatan Putaran Spindel Terhadap Kekasaran Permukaan pada Proses Bubut Mild Steel ST 37 - Yufrizal A; Eko Indrawan; Nofri Helmi; Abdul Aziz; Yoga Amanda Putra (invotek, 2019)
The surface quality of turning can be influenced by several factors such as determining the spindle rotation speed, determining cutting speed (cutting speed), cut angle. the purpose of this study was to compare the level of surface roughness in the mild steel ST 37 on lathe process. Every surface of the workpiece that undergoes a machining process will experience varying degrees of roughness. This research is an experimental study that compares the level of surface roughness of material material Mild Steel ST 37. Material that is done with a length of 70 mm, and turned into a diameter of 20 mm using 3 kinds of cutting angles and 3 kinds of spindle rotation speed. Measuring the surface roughness of the workpiece, namely surface tester mitutoyo SJ-201P. The results of this study can be concluded that the spindle rotation speed of 740 rpm with 80˚ cutting angle produces a smoother surface that is (∑Rap) = 5.76 μm or in the roughness class N9 while the spindle rotation speed is 440 rpm with 80 potong cutting angle produces a surface coarse (∑Rap) = 11.47 μm with N10 surface roughness class.